Adoption of the principle of ‘invitation to treat’ in Islamic law of contracts = Adoptasi prinsip pelawaan tawaran dalam kontrak undang-undang Islam - Jalil, Md. Abdul (UKM Press, 2012)
‘Invitation to treat’ looks similar to an offer in a contract but for business convenience and to protect the interests of sellers of goods, the courts have differentiated ‘invitation to treat’ from offer on policy grounds. The authors of ‘contract law’ in the United Kingdom and other common law countries have analyzed the principle of ‘invitation to treat’ and have accepted the rationale for its differentiation from ‘offer’ in contracts. Some Islamic scholars have opposed the differentiation and argued that ‘invitation to treat’ is in fact an offer and when accepted by the offeree, becomes a binding contract. However, their arguments for not accepting the rule of ‘invitation to treat’ are not very convincing. The objective of this article is to argue that there is acceptable rationale for differentiating an ‘invitation to treat’ from an offer and to propose that the principle of ‘invitation to treat’ can be adopted in Islamic law of contracts as it does not go against any shariah (Islamic law) principles.